The truth about finding and using customer momentum and the wisdom of crowds - Solomon, Michael R. (Truth about (FT Press), 2011)
"This Element is an excerpt from The Truth About What Customers Want (ISBN: 9780137142262), by Michael R. Solomon. How you and your customers are influenced by others (from celebrities to experts to groups) ... and what that means for marketing."--Resource description page.